2018
DOI: 10.1016/j.jcmg.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D Echocardiography-Derived Indices of Left Ventricular Function and Shape

Abstract: OBJECTIVES This study hypothesized that left ventricular (LV) ejection fraction (EF) and global longitudinal strain (GLS) derived from 3-dimensional echocardiographic (3DE) images would better predict mortality than those obtained by 2-dimensional echocardiographic (2DE) measurements, and that 3DE-based LV shape analysis may have added prognostic value. BACKGROUND Previous studies have shown that both LVEF and GLS derived from 2DE images predict mortality. Recently, 3DE measurements of these parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 24 publications
1
50
1
3
Order By: Relevance
“…In fact, identi cation of the predisposing factors for subclinical organ dysfunction provide the insight towards long-term risk of organ dysfunction. From a disease-prevention perspective, given the independent prognostic signi cance of TOD, it would make sense to establish screening strategies on IGE and implement intensive blood glucose management during young adulthood, avoiding irreversible organs damage [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, identi cation of the predisposing factors for subclinical organ dysfunction provide the insight towards long-term risk of organ dysfunction. From a disease-prevention perspective, given the independent prognostic signi cance of TOD, it would make sense to establish screening strategies on IGE and implement intensive blood glucose management during young adulthood, avoiding irreversible organs damage [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical target organ damages of hyperglycemia, indicated by coronary artery calcium (CAC), early cardiac deformation and dysfunction as well as albuminuria in our study, are e cient markers and well precursors of adverse clinical outcomes [4][5][6]. The Coronary Artery Risk Development in Young Adults (CARDIA) Study, which only enrolled young adults aged 18-30 years at baseline and underwent 6 blood glucose monitoring over 25 years, offers the opportunity to assess the impact of IGE on subclinical indicators of organ dysfunction in life-course pattern since young adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the prognostic value of 3D strain in myocardial infarction, hemodialysis, valvular heart disease, and a diverse variety of subjects [24,26,48,86,[97][98][99][100] (Table 6). These studies all showed that 3D global strains were impaired in patients who had cardiac events, and reduction of 3D global strains was associated with poor outcomes.…”
Section: Prognostic Valuementioning
confidence: 99%
“…Reduction of 2D and 3D strains was attributed to myocardial fibrosis or inflammation [101]. Three of eight studies directly compared prognostic values between 2D GLS and 3D GLS, and all three studies showed that 3D GLS had superior prognostic value over 2D GLS [26,99,100]. Further studies are needed to validate whether 3D GLS is distinctly superior to 2D GLS for predicting future outcomes in specific cardiovascular pathologies.…”
Section: Prognostic Valuementioning
confidence: 99%
See 1 more Smart Citation